Representation of Regret through Lexical Choices in Henry Moodie's Drunk Text: Fairclough's Critical Discourse Analysis Approach - Theresia Trisila Dewi; Zia Hisni Mubarak (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study analyzes the representation of the emotion regret in the lyrics of Henry Moodie’s song Drunk Text using Norman Fairclough’s Critical Discourse Analysis (CDA) framework. Employing a descriptive qualitative approach, the research examines eight selected lyric excerpts to highlight the dimensions of text, discourse practice, and social practice. The textual analysis focuses on how lexical choices, modality, pronouns, metaphors, and syntactic structures construct nuances of regret. The findings reveal eight recurring linguistic markers such as “nearly,” “forget it,” “wish,” and “afraid” which emphasize doubt, missed opportunities, and limited courage in communication. At the discourse practice level, the lyrics are produced as conscious linguistic constructions, distributed through digital platforms, and consumed by young audiences as reflections of their emotional experiences. At the social practice level, the lyrics illustrate the fragile communication culture of the digital generation, the ideology of fearful interpersonal relationships, and the role of pop music as a medium for articulating collective emotions.